UTILIZATION OF CROSSPUZZLE GAMES AS LEARNING MEDIA IN THE DEVELOPMENT OF THE MAHARAH KITABAH - Ana Lailatul Fitria; Muhammad Afton Ulin Nuha (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
Language is a communication tool. With language, we can talk to know each other. In addition to the local language and the national language, namely Indonesian, we also know foreign languages. Foreign Language is currently a compulsory subject for students at all levels of education. Most of the foreign languages spoken are English and Arabic. Many students experience difficulties in learning both foreign languages, especially in learning Arabic. In learning Arabic, there are four skills that must be mastered, namely maharah istima' (listening skills), maharah qiro'ah (reading skills), maharah kalam (speaking skills), and maharah kitabah (writing skills). Writing skill (maharah al-kitabah) is the highest skill of the four Arabic language skills. Writing is an activity related to thought processes and expression skills in written form. In order to make learning more efficient, an educator is required to be creative in conveying learning material, this is done so that learning writing skills becomes more fun and can help students in learning Arabic. One of the media that can be a solution is the crossword puzzle (TTS) game media. This study aims to explain the media for learning Arabic games in the form of crossword puzzles in maharah kitabah.